Mención Específica A Los Refranes Contenidos En El Noble Corán Y La Sagrada Biblia (Nuevo Testamento) - Imad Abedalkareem Ababneh (European Scientific Journal, ESJ, 2017)
This article is a specific comparative study between the proverbs of the two holy books, The Quran and The Bible. The proverbs or the Bible verses that compose this article, firstly appear in Spanish language in bold, and then the proverb or the qoranic verse in Arabic verse. Then in italic letter, the original transcription with the orthographic signs, and finally, the Spanish translation between “quotation mark”.